Institutional Unity vs Freedom of Expression: A Dissent Analysis of the Richardson Courts - Heine, Victoria (Victoria University of Wellington Law Review, 2002)
This paper undertakes an empirical analysis of the dissent patterns of the Court of Appeal during Sir Ivor Richardson’s Presidency (1996-2002) using the New Zealand Law Reports and Brookers Ltd electronic Court of Appeal decisions as the data set. Existing literature suggests that there are three main factors in whether a dissenting judgment would be given: judicial workload, the Court’s willingness to send out a clear message about the law, and the personalities and attitudes of individual judges. Dissents are also more likely to be common in discretionary decisions and the application of statutory principles. The results show a low rate of multiple judgments and rates of dissent in the Court of Appeal, seemingly as a result of an increase in judicial workload as well as the personality of individual judges.